The development and validation of an intervention for the improvement of academic performance and success of nursing students at a university in the Western Cape, South Africa - Katlego Dumisani Trevor Mthimunye; Felicity Megan Daniels (Elsevier, 2019)
A three round Delphi study aimed at developing and validating the intervention for improving the academic performance and success of undergraduate nursing students at a university in the Western Cape, South Africa was undertaken. This study forms the last phase of a larger study. The first round of the Delphi process used a self-developed semi-structured questionnaire focusing on rating the pre-developed prescriptive intervention statements that where identified from the preceding phases of the larger project as well as to obtain further recommendation from the panel of experts. The second round of the Delphi process focused on reviewing the items that did not reach the desired consensus (≥80%) as well as presenting the newly formulated prescriptive intervention statements based on the panel's recommendations provided in the first round of the Delphi process. The last round validated the intervention statements that reached the desired consensus (≥80%). The intervention highlighted that students need support in various aspects including: financial support, English language support, family support, theoretical and clinical support. Furthermore, the university has the responsibility to ensure the following: selection of quality prospective students, class attendance, university residence for nursing students, a student-friendly programme, uniformity and consistence in learning and teaching and lastly provide support to the educators. Keywords: Academic performance, Academic successes, Delphi, Intervention, Nursing education, Nursing students